On (??m, I)-statistical convergence of order - Savas, Ekrem; Et, Mikail (Springer, 2015)
In this paper we introduce the concepts of (Delta(m)(lambda), I)-statistical convergence of order alpha and [V](p) (Delta(m)(lambda), I)-summability of order alpha of real sequences and investigated between their relationship.
Keywords: Difference sequences; Statistical convergence; I-convergence; Cesaro summability